If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -11 = 4x + 16 Reorder the terms: -11 + x = 4x + 16 Reorder the terms: -11 + x = 16 + 4x Solving -11 + x = 16 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -11 + x + -4x = 16 + 4x + -4x Combine like terms: x + -4x = -3x -11 + -3x = 16 + 4x + -4x Combine like terms: 4x + -4x = 0 -11 + -3x = 16 + 0 -11 + -3x = 16 Add '11' to each side of the equation. -11 + 11 + -3x = 16 + 11 Combine like terms: -11 + 11 = 0 0 + -3x = 16 + 11 -3x = 16 + 11 Combine like terms: 16 + 11 = 27 -3x = 27 Divide each side by '-3'. x = -9 Simplifying x = -9
| 5-(6+9x)=(4x-1) | | 7.13=2(3.14)r | | 8x+7-3x=5+5x+2 | | 2x-8y-9x+5y= | | -8(-3s-6+8m)= | | X^2-4=45 | | x(x-4)-2=43 | | 77.4(0.681)= | | X+60=35 | | (2+v)(2v+3)=0 | | 3x(12x-5)-6x(6x-5)=0 | | 4x^3-9x^2+7x=2.5 | | 6x-17=2x+15 | | (√48)^(1/2) | | y=5-2n | | 8x-5y=2132 | | 2x+3(2x-5)=6 | | 13+3x=-91-10x | | 2x+15=4x+11 | | 34m-5-1/2m=1 | | 24-4x=9-7x | | X-(7x-8)= | | 8x-y=32 | | 5/6=1/x | | a+3b-4c=0 | | y=zx-2x+5 | | 18-x=x-2 | | 6y+2x=16 | | 5ex=15.76 | | (a+2b)(a^2-2ab+4b^2)= | | (m+1)(m^2-m+1)= | | (2a-b)(2a-b)= |